The effects of chemical components in the bath solution on mechanical properties of the electroplated coating on diamond tools. (2018) - Chen, Q.Q.; Cui, Z.M.; He, Q.S.; Wang, J.J.; Feng, C.J.
The bath compositions are critical to mechanical performance of the coating layer for electroplated diamond tools. In this paper, the effects of different chemical components in bath solution on mechanical properties including tensile strength and hardness of the electroplated coating were investigated by orthogonal experiments. The influences of different chemical components including nickel sulphate, cobalt sulphate and sodium chloride on mechanical properties of the electroplated coating were analysed. The results showed that increasing the component of nickel sulphate caused an unstable situation on tensile strength and hardness of the electroplated coating. However, hardness of the electroplated coating could be improved by increasing the component of cobalt sulphate. The concentration of sodium chloride had no obvious effect on mechanical properties of the electroplated coating layer. The experimental results revealed that the optimised bath compositions were at 270 g/L nickel sulphate, 20 g/L cobalt sulphate, and 10 g/L sodium chloride.